Is there any relation between intellectual capital and the capital structure of a company? The case of Polish listed companies - Monika Bolek; Katerina Lyroudi (e-Finanse: Financial Internet Quarterly, 2015)
This study investigates the relationship of the intellectual capital of a company (proxied by its intangible assets), with leverage and equity and capital structure. Our empirical results indicate that there is a negative relation between the intellectual capital (intangible assets) of a company and its leverage based on the Warsaw Stock Exchange main market and NewConnect alternative market. Moreover, the equity capital is found positively related to the level of intangibles in each of the two markets. These results support the thesis that intellectual capital (intangible assets) influences the capital structure of a company.
Keywords: G32; 330; intangible assets; intellectual capital; leverage; equity